Sunburn damage and stem and fruit water potential of apples (Malus domestica) ‘Brasil Gala’, ‘Cripps Pink’ and ‘Granny Smith’ - Vivian Severino; Santiago Dogliotti; Gerardo Echeverría; Erna Frins; Jaime González-Talice; José Antonio Yuri; Mercedes Arias-Sibillotte (Agrociencia Uruguay, 2024)
Fruit discards due to physiological disorders and mechanical damage can exceed 50% of apple production in neotropical climate zones such as Uruguay. These damages become generally visible during ripening and storage, but they depend on factors that occur in the field. Sunburn is a major quality defect in fruit, known to be related to high radiation and temperatures, and, more recently, it has also been related to the water status of tissues in fruit and trees. This study aimed to evaluate the relationship between fruit damage and fruit tissue water status in “Brasil Gala”, “Cripps Pink” and “Granny Smith”, as well as the effect of treatments to avoid sun damage (50% black net, 20% translucent white net and kaolinite application) on stemwater potential in “Granny Smith”. Fruit water potential decreased throughout the growth cycle. The exposed sides of fruits located outside the tree crown showed lower water potential than the non-exposed sides. Only the 50% black net of the sunburn avoidance treatments modified the water potential.